A Combined Water Extract of Frankincense and Myrrh Alleviates Neuropathic Pain in Mice via Modulation of TRPV1. (27th June 2017) - Hu, Danyou; Wang, Changming; Li, Fengxian; Su, Shulan; Yang, Niuniu; Yang, Yan; Zhu, Chan; Shi, Hao; Yu, Lei; Geng, Xiao; Gu, Leying; Yuan, Xiaolin; et al.
Abstract : Frankincense and myrrh are widely used in clinics as a pair of herbs to obtain a synergistic effect for relieving pain. To illuminate the analgesia mechanism of frankincense and myrrh, we assessed its effect in a neuropathic pain mouse model. Transient receptor potential vanilloid 1 (TRPV1) plays a crucial role in neuropathic pain and influences the plasticity of neuronal connectivity. We hypothesized that the water extraction of frankincense and myrrh (WFM) exerted its analgesia effect by modulating the neuronal function of TRPV1. In our study, WFM was verified by UHPLC-TQ/MS assay. In vivo study showed that nociceptive response in mouse by heat and capsaicin induced were relieved by WFM treatment. Furthermore, thermal hypersensitivity and mechanical allodynia were also alleviated by WFM treatment in a chronic constriction injury (CCI) mouse model. CCI resulted in increased TRPV1 expression at both the mRNA and protein levels in predominantly small-to-medium neurons. However, after WFM treatment, TRPV1 expression was reverted in real-time PCR, Western blot, and immunofluorescence experiments. Calcium response to capsaicin was also decreased in cultured DRG neurons from CCI model mouse after WFM treatment. In conclusion, WFM alleviated CCI-induced mechanical allodynia and thermal hypersensitivity via modulating TRPV1.